Internal evaluation and its roles in improving the quality of technique & engineering training, Case: Department of Technique and Engineering Faculty at Shahed University - Majid Darabi; Faranak Mokhtarian; Mohsen Farmahini Farahani; Korosh Esmaeili (آموزش مهندسی ایران, 2012)
Internal evaluation is a process in which faculty members of departments make judgments about their own performance and plan to improve their future activities. Internal evaluation in the department can be an effective step for increasing the quality of higher education system. Internal evaluation with data collection, analysis and feedback, supports management in decision-making. As internal evaluation project has been performed and approved in different departments of technique & engineering faculty at Shahed University. In the present paper the meta-analysis of the reports are presented. These departments include: 1) Department of Electrical Engineering 2) Department of Computer Engineering and3) Department of Medical Engineering. Data have been collected by analyzing internal evaluation reports. At the end, a framework for improving the quality of teaching and research has been recommended